Uric acid detection in visible spectrum - Afiqah Yaacob; Nor Hafizah Ngajikin; Nurfatihah Che Abd Rashid; Siti Hajar Aminah Ali; Maslina Yaacob; Suhaila Isaak; Noran Azizan Cholan (Universitas Ahmad Dahlan, 2020)
The measurement of uric acid based on the optical absorption at visible light spectrum is investigated and tested. Sensing in the visible region was conducted for determination of suitable wavelength that produces high sensitivity and accuracy performance based on the Beer-Lambert law calculation. In this work, the uric acid is detected by detecting sodium urate as a product of chemical reaction between uric acid with sodium hydroxide buffer. The setup has been tested for uric acid concentration ranging from 15 mg/dL to 85 mg/dL. Three wavelengths have been analyzed which are 460 nm, 525 nm and 630 nm. Measured data at 460nm wavelength exhibits the highest sensitivity, which is 0.0012 (mg/dL)-with 86.51% accuracy. Detection of uric acid at visible light spectrum offers a low-cost sensor based on visible LEDs and photodiode is possible to be realized.